Desviación, disciplina social e intervenciones judiciales en el Antiguo Régimen - Mantecón Movellán, Tomás Antonio (Studia Historica: Historia Moderna, 2009)
RESUMEN: Durante la Edad Moderna se dio en Europa una expansión de la ciencia de la ciencia penal y de desarrollo de los aparatos judiciales. Este proceso ha sido llamado de penalización o incriminación, incluso revolución jurídica. Cantabria ofrece un modelo particular de concreción de este proceso. En esta regla española estuvieron vigentes en el Antiguo Régimen formas privadas de justicia, formas que eran legitimadas por la costumbre, aunque escaparan a los jueces, y formas que aproximan el ejemplo cántabro al de algunas regiones rurales del Norte de Europa como las escocesas, finlandesas y polacas. Sin embargo, las intervenciones judiciales fueron más numerosas en Cantabria que en esas otras áreas europeas, y parecidas a las del área rural holandés. La trayectoria del número de causas judiciales en la región española citada es un excelente indicador de la evolución de la conflictividad social, pues el número de pleitos se manifestó con gran independencia del crecimiento de la población en los siglos XVII y XVIII. Además, los habitantes de Cantabria acudían a los jueces, incluso en los años más ásperos, con el fin de lograr un arbitraje de los jueces tendente a facilitar negociaciones entre las partes fuera de los juzgados. Todo esto hizo que en Cantabria ocurrieron más actos judicíales que en otras regiones rurales europeas, también hizo que pervivieran formas consuetudinarias de corrección o disciplina de la desviación social e, igualmente, hizo que esas formas disciplinarias afectaran al significado de términos como desviación social o crimen. Este es el principal asunto de este artículo. ABSTRACT: During the lóth, 17th and 18 th centuries there was an expansion of penal law and a development of judicial intimions in Europe. This general process has been thought as it was a slow judicial revolution. In Cantabria it had a particular shape. There were private versions of justice out of the court in this Spanish region. The private justice had its legitimation in local customs. Another rural regions of Europe, such as Scotland, Finland or Poland, had a very important framework of private justice too. All these cases also point out a competition between the penal law and the local custom. Nevertheless, we can still see differences between Cantabria and the others. One of these differences was the ratio between the population rates and the number of judicial actions. In Cantabria this relationship was more similiar to the rural areas of Holland, which had smaller judicial districts than the others. The trend of judicial actions in Cantabria is a very good indicator of how the social struggles were changing along the time. Moreover, w can add others evidences for this argument, because, first, the relationship between population trend and judicial actions tendency was weak in Cantabria during the 17th and 18th centuries. Secondly, the people of Cantabria went to the court even in the worst times. Therefore, neither the population trend nor the harshest circumstances were distorting the rates of conflict in the courts. In most of the cases, after the beginning of the juditial action, the solution was out of the court but with the arbitration of the judge. All of these reasons let show us why there were more judicial actions in Cantabria than in some other rural areas of Europe such asScotland, but these reasons also show how strong the customary means of social discipline were against the deviant behaviour. If we know the way in which all these questions were linked each other along the time we will know how the social meaning of deviance and crime in a rural context and in preindustrial time was. This is the point in this article.